Implementation of Emergency Response Management in Large-Scale Construction Projects: Literature Review - Zakwan, M. Hadin; Maghfirah, Suci; Marpaung, Fadhlan Al Hafiz; Hasibuan, Abdurrozzaq (AMK : Abdi Masyarakat UIKA, 2025)
Emergency Response Management (ERM) is a critical aspect of large-scale construction projects, where the risk of accidents and incidents can significantly impact worker safety, project continuity, and the company's reputation. This article aims to conduct a systematic literature review on the implementation of Emergency Response Management in the context of large-scale construction projects. By analyzing various relevant studies, this research identifies best practices, challenges, and factors influencing the effectiveness of Emergency Response Management. The review findings indicate that the success of ERM implementation highly depends on employee training, top management involvement, and the integration of emergency response plans into the organization’s safety culture. Additionally, the study finds that the use of modern technology, such as management information systems and simulations, can enhance preparedness and response to incidents. The research also highlights the need for further studies to develop a comprehensive ERM framework that can be adapted across different construction project contexts.